Identification and expression analysis of antigenic sites of hepatitis C virus genotype 3a NS3 and NS5A genes of local isolate - Sabeen Sabri (Egyptian Liver Journal, 2021)
Abstract Background Hepatitis C virus, a silent killer, has infected 71 million people globally. The recombinant viral antigenic proteins might be used in the early diagnosis of HCV infection. The NS3 and NS5A genes of HCV function in HCV replication and influence host cellular factors that are involved in HCV pathogenesis. The current study was designed to select NS3 and NS5A antigenic sites, amplified, cloned, and expressed in order to find out better assays for diagnosis or drug and vaccine development. The antigenic sites within NS3 and NS5A genes were selected and confirmed through sequencing and were cloned. The antigenic recombinant proteins were expressed in bacterial strain E. coli BL21ply*, and the expression was confirmed by western blotting by using gene-specific and vector-specific antibodies. Results Specific antigenic regions within the NS3 and NS5A genes of the HCV 3A genotype were amplified. PCR results showed 328 bp and 747 bp antigenic regions, respectively. The regions were confirmed by DNA sequencing and cloned into a bacterial expression vector. Expression analysis showed 12 kDa and 28 kDa of NS3 and NS5A antigenic recombinant proteins, respectively. Taken together, these studies will help to analyze the genetic variability within the local HCV isolates as these antigenic recombinant proteins were quite important in the screening of HCV-infected patients. Conclusions This study might help to enhance the progress in the treatment of HCV infection through the modeling of HCV non-structural genes (NS3 and NS5A) from local isolate, and it might also present the viral genes as potential therapeutic targets.